Direct User Guidance in e-Dictionaries for Text Production and Text Reception — The Verbal Relative in Sepedi as a Case Study - Prinsloo, D.J.; Bothma, Theo J.D.; Heid, Ulrich; Prinsloo, Daniel J. (Lexikos, 2017)
This article introduces a prototype of a writing (and learning) assistant for verbal relative clauses of the African language Sepedi, accessible from within a dictionary or from a word processor. It is an example of how a user support tool for complicated grammatical structures in a scarcely resourced language can be compiled. We describe a dynamic light-weight tool aimed at combining user-knowledge with text production support, i.e., user-involved interactive text production of the complicated verbal relative in Sepedi. In this article, the focus is on access in a dictionary use situation. Although the tool is intended as a writing assistant to support users in text production; it also satisfies text reception and cognitive needs, but its focus is on solving text production issues related with the interaction between lexical items and complex grammatical structures in the African (Bantu) languages and for learning by users and/or training users in this interaction.